The Image of Political Conflict: Evaluation Semantic Universals in Students’ Individual Mind - Virna, Zhanna (East European Journal of Psycholinguistics, 2014)
The paper is focused on the study of the political conflict image from the perspective of psychosemantics. The integral psychosemantic approach to the political conflict allowed establishing semantic universals viewed as students’ evaluation of the conflict’s image. Among the parameters were active, dangerous, open, rational, moral, close, aggressive, etc. The results of the students’ semantic space study through the semantic differential showed that the semantic constructs of “political conflict” image as reflected in the minds of the students, and “real political conflict” image are different, since the reality is able to change their cognitive interpretation and emotional attitude.ReferencesAktualnye Problemy Deyatelnosti Mezhdunarodnykh Organizatsii. (1982). [Key Issues ofInternational Organizations Activity] G. Morozov, Ed. Moscow: Mezhdunarodnye Otnosheniya.Vasylenko, A. P. (1993) Viiskovo-politychnyi konflikt – meta chy zasib polityky. [Militarypolitical conflict – A goal or means of politics] Politychna Dumka, 4, 6-12.Zinchenko, V. P. (1991). Miry soznaniya i struktura soznaniya. [Worlds of mind and structure ofmind]. Voprosy Psikhologii, 2, 15–34.Leontyev, A. N. (1975). Deyatelnost’. Soznaniye. Lichnost. [Activity. Mind. Personality].Moscow: Politizdat.Petrovsky, A. V. (1982). Lichnost. Deyatelnost. Kollektiv [Peronality. Activity. Collective].Moscow: Pedagogika.Psihologiya. Slovar (1990). [Psychology Dictionary], A. Petrovsky, M. Yaroshevsky, Eds.Moscow: Politizdat.Serkin, V. P. (2004). Metody Psihosemantiki. [Methods of Psychosemantics]. Moscow:AspektPress.Smirnov, S. D. (1985). Psihologiya Obraza: Problema Aktivnosti Psikhicheskogo Otrazheniya.Moscow: Moscow University Publishers.Traiditional Interstate and Internal Conflicts in Post-Bipolar System of International relations[Electronic resource]. Retrieved 14.04.2014 from http: www.cirs.kiev.ua./index.php?cmd=index/Page&page=0303a.Cottam, M. (1986). Foreigh Policy Decision-Making: The Influence of Cognition. Boulder:Westview.
Keywords: individual mind; world image; semantic universals; political conflict image; real political conflict image; student youth.